The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/ijms23137052
|View full text |Cite
|
Sign up to set email alerts
|

Muscle and Adipose Tissue Communicate with Extracellular Vesicles

Abstract: In numerous body locations, muscle and adipose tissue are in close contact. Both tissues are endocrine organs that release cytokines, playing a crutial role in the control of tissue homeostasis in health and diseases. Within this context, the identification of the signals involved in muscle–fat crosstalk has been a hot topic over the last 15 years. Recently, it has been discovered that adipose tissue and muscles can release information embedded in lipid-derived nanovesicles called ‘extracellular vesicles’ (EVs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 69 publications
(103 reference statements)
0
14
0
Order By: Relevance
“…However, few studies on the exosomes in meat products have been reported. Exosomes are present in muscle and fat of animals in vivo is an indisputable fact [20]. The process of exosomegenesis involves the invaginations of the plasma membrane and the formation of intracellular multivesicular bodies [3].…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies on the exosomes in meat products have been reported. Exosomes are present in muscle and fat of animals in vivo is an indisputable fact [20]. The process of exosomegenesis involves the invaginations of the plasma membrane and the formation of intracellular multivesicular bodies [3].…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, adipose-derived exosomes were first found, which can act as a mode of communication between AT and macrophages [ 53 ]. After that, accumulating evidence indicated that adipose-derived exosomes can transfer specific cargoes from cell to cell via paracrine or endocrine signaling, thereby regulating metabolic inflammation, energy metabolism, and insulin sensitivity of skeletal muscle [ 24 , 54 ]. At present, the study of AT-derived exosomes on skeletal muscle mainly focuses on the research of the cargoes (proteins and miRNAs) contained in the exosomes.…”
Section: Adipose-derived Exosomes In Adipocyte–myocyte Crosstalkmentioning
confidence: 99%
“…In the pathological context, insulin resistance is a key component in the etiology of type 2 diabetes. As the major insulin-sensitive tissues, skeletal muscle was proved to be regulated by adipose-derived exosomes with their cargo during the development of insulin resistance [ 24 ]. Proteomic characterization of adipocytic exosomes from diabetes animal models (OLETF) and controls (LETO) were firstly performed in rats.…”
Section: Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite evidence suggesting a diverse range of distinct regulatory functions for myoblast and myotube SM-EVs, the majority of studies to date have typically isolated heterogeneous EV fractions using protocols such as ultracentrifugation or precipitation that have often not accounted for the presence and contribution of co-isolated components such as lipoproteins and RNA binding proteins (e.g. AGO2) routinely identi ed in EV studies due to the lack of an optimal isolation method (23)(24)(25). As such, optimising effective SM-EV isolation methods with high levels of purity will be important if we are to accurately de ne their composition and functional effects in physiological and pathophysiological systems.…”
Section: Introductionmentioning
confidence: 99%